EXPOSURE TO WHOLE-BODY VIBRATION IN FORWARDER OPERATORS IN EUCALYPTUS HARVESTING - de Oliveira, Felipe Martins; Rodrigues, Carla Krulikowski; Lopes, Eduardo da Silva; Fiedler, Nilton César (Floresta, 2025)
Mechanized log extraction in wood harvesting can cause exposure to whole-body vibration (WBV) and several health problems for operators. In this context, the aim was to assess the levels of exposure to WBV when harvesting logs using a forwarder who worked day and night shifts and considering different elements of the work. The study was carried out in a forestry company in Southern Brazil that harvested eucalyptus stands. We conducted a time study considering five work elements: empty trip, loading, loaded trip, unloading and non-productive time. Vibration data was obtained using a WBV meter, with a triaxial accelerometer (x, y and z axes) installed inside in the seatpad of the machine. To assess the WVB, the method proposed by the Brazilian Occupational Hygiene Standard (NHO 09) was used, calculating the acceleration resulting from normalized exposure (aren) and the resulting vibration dose value (VDVR). The average values of the times consumed with the partial activities were compared by the Tukey test (α ≤ 0.05). Occupational exposure to WBV in forwarder operators (aren 0.85 and 0.78; VDVR 18.7 and 18.8 for day and night shifts, respectively) was below the limits considered emergency (aren 1.1 and VDVR 21), however, preventive measures were shown to be necessary to avoid increasing levels. The most harmful work elements of the operational cycle, in terms of exposure to WBV, were those in which the forwarder moved around the stand, as empty and loaded trips.